Introduction: crossing african borders – migration and mobility - Rodrigues, Cristina Udelsmann (2013)
This publication is one of the results of a conference organised in Lisbon in 2011 on the theme of African borders and their relationships with migration and mobility. The selected papers are a sample of the diverse perspectives on the general theme presented at the meeting. Other written contributions were presented at the event and summaries of them can be found online.